Assessing the impact of governance and health expenditures on carbon emissions in China: Role of environmental regulation - Wang, Yue; Liu, Mengjie; Wang, Shan; Cui, Xiuping; Hao, Lei; Gen, HaSiBa (Frontiers in Public Health, 2022)
The current study tries to summarize the leading factors and their behavior toward the environmental quality. Therefore, this study investigates the environment-development linkage in China's economy covering the period of 1984–2018. In order to investigate the proposed objectives, the current study uses the dynamic ordinary least square, fully modified ordinary least square and canonical co-integration regression with granger causality test. The results reveal that there exists an inverted U-shaped relationship in China's economy. Likewise, urbanization positively contributes to environmental deterioration. Furthermore, the health expenditures also cause to deteriorate the environmental quality. In contrast, there exists the negative association between good governance and carbon emissions, while the rule of law in China's economy does not secure the environmental quality. Therefore, environmental regulation policies need to be revised in order to achieve a sustainable environment. As a result, we recommend that China continue to expand its economy and invest in health care and environmental initiatives.